THE USE OF STORYTELLING IN SPEAKING INSTRUCTION - Ririn Meylinda Purwasari; Sidik Indra Nugraha (PROJECT (Professional Journal of English Education), 2023)
Speaking is one of the essential skills that EFL students should master to communicate in English. However, speaking remains challenging to the majority EFL students especially in Indonesian context. This research is aimed at investigating the ways storytelling facilitates students in learning to speak, and discovering the  students’ experiences in using storytelling as a technique in learning to speak. Four students and one English teacher were purposefully selected to be research participants. The data were collected through observation and interviews, and analyzed qualitatively using thematic analysis (Braun & Clark, 2006; Riger & Sigurvinsdottir, 2016). The results showed that storytelling: (a) is an appropriate technique for students to learn pronunciation and vocabulary as well as speaking fluency; (b) amplifies students' understanding of the text; (c) activates students cognition to learn and practice speaking English; and (d) contributes to alleviate students' speaking anxiety, and to improve students' speaking confidence as well. Furthermore, storytelling resulted in a valuable experience for students in learning to speak. Keywords:  Storytelling; Teaching Technique; Learning Speaking